Data Sharing Application with SMS Notification - Bernardus Satrio Palapessy, 2Nur Hadisuk Satrio Palapessy; Nur Hadisukmana (IT for Society, 2016)
The result of the research is the application that allow user to retrieve information through News and Event Agenda Feature. This application also allows the member to keep in touch with their stuff with SMS notification. The application is easy to control by an administrator through a message system and capabilities of administrator of any file, also by a user hierarchy system.